3z + 6
3z and 6 has greatest common factor, that is 3. Divide 3z and 6 by the greatest common factor (3).
3z ÷ 3 = z
6 ÷ 3 = 2
So, we could work on the expression as following.
3z + 6
= 3 × z + 3 × 2
From the expression above, we should separate 3 from z and 2 by a parenthesis to make distributive property.
3 × z + 3 × 2
= 3(z + 2)
SUMMARY
3z + 6
= 3 × z + 3 × 2
= 3(z + 2)
<span>1.69 divide by 1000</span><span> =0.00169
169/100 = 1.69 meters
1690/1000=1.69
so the first one is not same
hope it helps</span>
Answer: $5.25
Step-by-step explanation:
25/100 = 0.25
0.25 * 7 = 1.75
7 - 1.75 = 5.25
Answer:
2/3
Step-by-step explanation:
Answer:
220
This should be correct since you are multiplying by 2